Producing a plant diversity portal for South Africa. Issue 2 (14th April 2017) - le Roux, M. Marianne; Wilkin, Paul; Balkwill, Kevin; Boatwright, J. Stephen; Bytebier, Benny; Filer, Denis; Klak, Cornelia; Klopper, Ronell R.; Koekemoer, Marinda; Livermore, Laurence; Lubke, Roy; Magee, Anthony R.; et al.
Abstract: Taxonomy provides a universal method to classify biodiversity at different scales locally and globally. Currently, existing taxonomic treatments are scattered, limiting their accessibility and utility. The Convention on Biological Diversity has responded to this challenge by setting the goal of compiling a World Flora Online (Global Strategy for Plant Conservation Target 1, 2011–2020). This can be done by aggregating electronically available information provided by each country, region or specialist group. Developing a Flora or a high‐level monographic product requires time and input from a large pool of taxonomic specialists. Completing a Flora may be difficult to accomplish for phytodiverse countries, such as South Africa, if the 2020 target is to be met. Fortunately, a large number of taxonomic contributions and many electronic tools exist that can enhance progress. Where these are available, efforts have to be made to access and digitise the literature. Here we describe a pragmatic approach to developing an online Flora, involving taking floristic information from multiple, previously published sources, digitising the legacy literature where needed and aggregating the required information into a single portal. South Africa is committed to producing an online Flora (the e‐Flora of South Africa) and contributing the information to the World Flora Online initiative following the aggregator portal approach, a method described here that might be useful for other countries with high phytodiversity.